CHITOSAN PREPARATION WITH MULTISTAGE DEACETYLATION OF CHITIN AND INVESTIGATION OF ITS PHYSICOCHEMICAL PROPERTIES - Ahmad Budi Junaidi; Indriana Kartini; Bambang Rusdiarso (Indonesian Journal of Chemistry, 2009)
Study of chitosan prepared with chitin deacetylation by multistage alkali treatments has been done. Chitin was extracted from Lampung white shrimp's (Litophenaeus vannamei) shell. The FTIR spectroscopy was used to determine deacetylation degree of chitin/chitosan. Viscometry was used to determine molecular weight of chitosan. Effect of chitin deacetylation by multistage alkali treatments toward deacetylation degree and molecular weight was studied by comparingit with continuous alkali treatment. The results showed that chitosan prepared by multistage alkali treatment had higher deacetylation degree than those of obtained by continuous alkali treatment. Multistage alkali treatment does not influence the chitosan's molecular weight. Despite its significant effect on the deacetylation process, concentration of alkali does not significantly effect the process of depolimerization.